the degree of use of educational means and techniques in teaching computer subject in secondary schools, obstacles to their use, and their relationship to students' motivation towards learning (Journal of the College of Basic Education, 2023)
The study aimed to identify (the degree of use of educational means and techniques in teaching computer subject in secondary schools, obstacles to their use, and their relationship to students' motivation towards learning).In Baghdad Governorate - Directorate of Education, Rusafa, the third, as the researcher used the descriptive approach for its suitability to the subject of the research. The research community has reached (132) male and female teachers, while the research sample has reached (26) male and female teachers, 10 (males) and 16 (females). With five alternatives (largely agree, somewhat agree, agree, disagree, and strongly disagree), the values of the alternatives were (1-5), as well as a measure of the obstacles to the use of means and techniques. The number of its paragraphs was (11). The validity and reliability of all tools were verified The researcher used statistical methods (the arithmetic mean, standard deviation, analysis of variance and Pearson's correlation coefficient) and the results showed:The degree of use by secondary school teachers of educational means and techniques got a weak degree, as it turned out that the level of use of educational means and techniques is very weak, due to the availability of means and techniques in specific classrooms, which makes their use very limited, as well as the lack of educational devices in schools and the level of students’ motivation towards Computer learning was very weak. The researcher recommended a number of recommendations and proposals.